Julia eaudiobook A novel. - Newman, Sandra (HarperAudio, 2023)
A PEOPLE Magazine Must-Read Book for Fall 2023 | An Esquire Best Book of Fall 2023 | A Guardian Biggest New Book of 2023 | A LitHub Most Anticipated Book of 2023 An imaginative, feminist, and brilliantly relevant-to-today retelling of Orwell's 1984, from the point of view of Winston Smith's lover, Julia, by critically acclaimed novelist Sandra Newman. Julia Worthing is a mechanic, working in the Fiction Department at the Ministry of Truth. It's 1984, and Britain (now called Airstrip One) has long been absorbed into the larger trans-Atlantic nation of Oceania. Oceania has been at war for as long as anyone can remember, and is ruled by an ultra-totalitarian Party, whose leader is a quasi-mythical figure called Big Brother. In short, everything about this world is as it is in Orwell's 1984. All her life, Julia has known only Oceania, and, until she meets Winston Smith, she has never imagined anything else. She is an ideal citizen: cheerfully cynical, always ready with a bribe, piously repeating every political slogan while believing in nothing. She routinely breaks the rules, but also collaborates with the regime when necessary. Everyone likes Julia. Then one day she finds herself walking toward Winston Smith in a corridor and impulsively slips him a note, setting in motion the devastating, unforgettable events of the classic story. Julia takes us on a surprising journey through Orwell's now-iconic dystopia, with twists that reveal unexpected sides not only to Julia, but to other familiar figures in the 1984 universe. This unique perspective lays bare our own world in haunting and provocative ways, just as the original did almost seventy-five years ago.